Producing and directing the short film and video - Rea, Peter W.; Irving, David K. (Burlington, MA : Focal Press, 2015)
This is the definitive book on the subject for the serious film student or beginning filmmaker. Its unique two-fold approach looks at filmmaking from the perspectives of both the producer and director, and clearly explains how their separate roles must work together to create a successful short film or video. Through extensive examples from award-winning shorts and insightful interviews, you will learn about common challenges the filmmakers encountered during each step of filmmaking process, from preproduction to production, postproduction, and distribution and the techniques they used to overcome them.
Introduction -- Timeline -- Preproduction. Script -- Finance -- Breakdowns -- Schedule -- Budget -- Crew -- Actors -- Location -- Art direction -- Camera -- Sound -- Production. On set -- Postproduction. Pix postproduction -- Sound postproduction -- Finishing/Online/Laboratory -- Distribution/Exhibition -- Appendix A. Script sample -- Appendix B. Safety issues -- Appendix C. Music clearance and insurance -- Appendix D.A short history of the short film -- Appendix E. Genres -- Appendix F. Screening list -- Appendix G. Film and media programs -- Appendix H. Where are they now?
Includes bibliographical references and index.
Keywords: Short films -- Production and direction; Video recordings -- Production and direction